KEDISIPLINAN SISWA DALAM BELAJAR PENDIDIKAN AGAMA ISLAM PADA MASA NEW NORMAL DI SMK N 1 TILATANG KAMANG - Zikra Azhura Aulia; Iswantir Iswantir; Salmi Wati; Zulfani Sesmiarni (Universitas Pahlawan Tuanku Tambusai, 2022)
This research is motivated by student discipline problems, in learning activities the authors take samples in class XI TKJ. Student discipline is still not newly formed in the New Normal period. The role of an educator must be active in giving tips to students who are less disciplined. Questions from research. How are PAI teachers' tips for applying discipline to class XI TKJ students at SMKN 1 Tilatang Kamang, Agam Regency . teacher's obstacles in conducting discipline for class XI TKJ students. This research uses qualitative research, using qualitative descriptive research methods. Sources of data obtained through key informants, namely students of class XI TKJ and supporting informants, namely PAI teachers and student representatives at SMKN 1 Tilatang Kamang. In collecting data using observation and interviews. Data analysis uses data reduction, data presentation and data levers. The results of this study are the teacher's tips for applying discipline to PAI subjects in class XI TKJ at SMKN 1 Tilatang Kamang through the results that the teacher strengthens the student's discipline character, pays attention to students, makes strict rules, gives clear directions. clear, giving sanctions, giving tolerance, members for student character, class management, finding problem points, controlling, connecting books, obstacles faced by many students who lack discipline, teacher control is not optimal. Keywords: PAI Student Discipline, New Normal